Early fluctuations in busulfan levels with therapeutic dose monitoring during allogeneic stem cell transplantation: do they matter?. Issue 8 (3rd July 2019) - Jain, Tania; Kunze, Katie L.; Khetarpal, Banveet K.; McCallen, Margaret R.; Betcher, Jeffrey A.; Ofori, Henry T.; Khera, Nandita; Slack, James L.; Leis, Jose F.; Sproat, Lisa Z.; Noel, Pierre; Palmer, Jeanne
Abstract: Therapeutic dose monitoring is widely adopted for determination of busulfan (Bu) dose for use as a conditioning regimen. However, while dose adjustments are being incorporated, transient fluctuations of Bu levels may occur. We aim to understand if these fluctuations affect clinical outcomes of these patients. We compared outcomes in patients in whom the absolute dose changes and fluctuation of AUC were ≥ median% versus < median%. Rates of sinusoidal obstructive syndrome, grades 2–4/grades 3–4 acute and chronic graft versus host disease were not different between the two cohorts. The Kaplan–Meier curves for overall survival showed no significant differences. Six patients required >50% dose adjustment and four had a fluctuation in AUC of >50%. One of these patients died of sinusoidal obstruction syndrome and two died of infections. In our study, the transient fluctuations in Bu levels did not affect clinical outcomes; hence obviating the need for test dose strategy.